Potential to Increase Productivity and Sustainability in Argentinean Agriculture with Controlled Traffic Farming: A Short Discussion - Antille, Diogenes L. (2015)
Drivers for and potential barriers against adoption of controlled traffic farming (CTF) systems in Argentina are reviewed. Trafficcompaction is one of the main factors affecting crop productivity within Argentinean agriculture, and has significant althoughless quantified impacts on the whole-of-farm system. This suggests that the benefits of no-tillage (NT), which represents thedominant form of cropping in Argentina, are not fully realised. Conservative estimates indicate that crop yields could be improvedby at least 15% if NT is used in conjunction with CTF. Cost-benefit analyses of available options for compaction management arerequired. Despite this, and based on reported evidence internationally, a shift toward increased uptake of CTF within Argentineanagriculture is likely to: (1) improve productivity and farm profitability, (2) enhance environmental performance, and (3) maintaincompetitiveness of the agricultural sector. Appropriate technical advice and support is a key requirement to drive adoption of CTF. Therefore, the adoption process will benefit from collaboration developed with well-established research and extensionorganisations in Australia and the United Kingdom, and active engagement of machinery manufacturers.